ANALYSIS THE USE OF CODE SWITCHING AND CODE MIXING IN INSTAGRAM CAPTIONS OF INDONESIAN ARTISTS - Nose, Asmida (Journal of Islamic Culture and Literature (JICeL), 2024)
The purpose of the study is to analyze the codes switching and code mixing in the caption of Indonesian celebrity. The study USES the qualitative method and USES the code switching theory from hoffman (1991: 112) and USES the code mixing theory from muysken (2000). Studies are conducted on the social media object of instagram and are searching for captions of Indonesian artists. Studies have shown that switching and mixing codes on Indonesian celebrity instagram also reflect cultural and linguistic dynamics happening in society. They point to language adaptation and flexibility in the digital age, where a mixture of languages has become common in everyday communication. It also reflects social changes and globalization that affect the way people communicate and interact in social media.Keywords: code switching, code mixing, caption, Instagram